Anaerobic digestion of thermal pretreated brewers' spent grains. Issue 4 (6th April 2015) - Bochmann, G.; Drosg, B.; Fuchs, W.
<x xml:space="preserve">Abstract</x> Anaerobic digestion offers a good opportunity to degrade residues from breweries to biogas. To improve the anaerobic degradation process thermal pretreatment of brewers' spent grains (BSG) offers the opportunity to increase degradation rate and biogas yield. Aim of the work is to show the influence of the thermal pretreatment of BSG to anaerobic digestion. BSG were pretreated at different temperature levels from 100 to 200°C. The biogas production of thermally pretreated BSG lies between 30 and 40% higher than for untreated reference. The temperature of the pretreatment process has a significant influence on the degradation rate or gas yield, respectively. Up to a temperature of 160°C, the biogas yield rises. Temperatures over 160°C result in a slower degradation and decreasing biogas yield. Substrate with and without pretreatment gave a daily biogas yield of 430 and 389 Nm3 × kg−1 VS, respectively. Batch analysis of the biochemical methane potential gives a total methane yield of 409.8 Nm3 CH4 × kg−1 VS of untreated brewers' spent grains and 467.6 Nm3 CH4 × kg−1 VS of the pretreated samples. For pretreatment energy balance estimation has been carried out. Without any heat recovery demand is higher than the energy surplus resulting from pretreatment of BSG. With energy recovery by heat exchanger the net energy yield could be increased to 38.87 kWh × kg−1 FM or 8.81%. © 2015 American Institute of Chemical Engineers Environ Prog, 34: 1092–1096, 2015